Improved risk stratification of patients with atrial fibrillation: an integrated GARFIELD-AF tool for the prediction of mortality, stroke and bleed in patients with and without anticoagulation. Issue 12 (21st December 2017) - Fox, Keith A A; Lucas, Joseph E; Pieper, Karen S; Bassand, Jean-Pierre; Camm, A John; Fitzmaurice, David A; Goldhaber, Samuel Z; Goto, Shinya; Haas, Sylvia; Hacke, Werner; Kayani, Gloria; Oto, Ali; et al.
Abstract : Objectives: To provide an accurate, web-based tool for stratifying patients with atrial fibrillation to facilitate decisions on the potential benefits/risks of anticoagulation, based on mortality, stroke and bleeding risks. Design: The new tool was developed, using stepwise regression, for all and then applied to lower risk patients. C-statistics were compared with CHA2 DS2 -VASc using 30-fold cross-validation to control for overfitting. External validation was undertaken in an independent dataset, Outcome Registry for Better Informed Treatment of Atrial Fibrillation (ORBIT-AF). Participants: Data from 39 898 patients enrolled in the prospective GARFIELD-AF registry provided the basis for deriving and validating an integrated risk tool to predict stroke risk, mortality and bleeding risk. Results: The discriminatory value of the GARFIELD-AF risk model was superior to CHA2 DS2 -VASc for patients with or without anticoagulation. C-statistics (95% CI) for all-cause mortality, ischaemic stroke/systemic embolism and haemorrhagic stroke/major bleeding (treated patients) were: 0.77 (0.76 to 0.78), 0.69 (0.67 to 0.71) and 0.66 (0.62 to 0.69), respectively, for the GARFIELD-AF risk models, and 0.66 (0.64–0.67), 0.64 (0.61–0.66) and 0.64 (0.61–0.68), respectively, for CHA2 DS2 -VASc (or HAS-BLED for bleeding). In very low to low risk patients (CHA2 DS2 -VASc 0 or 1 (men) and 1 or 2 (women)), the CHA2 DS2 -VASc and HAS-BLED (for bleeding) scores offered weak discriminatory value for mortality, stroke/systemic embolism and major bleeding. C-statistics for the GARFIELD-AF risk tool were 0.69 (0.64 to 0.75), 0.65 (0.56 to 0.73) and 0.60 (0.47 to 0.73) for each end point, respectively, versus 0.50 (0.45 to 0.55), 0.59 (0.50 to 0.67) and 0.55 (0.53 to 0.56) for CHA2 DS2 -VASc (or HAS-BLED for bleeding). Upon validation in the ORBIT-AF population, C-statistics showed that the GARFIELD-AF risk tool was effective for predicting 1-year all-cause mortality using the full and simplified model for all-cause mortality: C-statistics 0.75 (0.73 to 0.77) and 0.75 (0.73 to 0.77), respectively, and for predicting for any stroke or systemic embolism over 1 year, C-statistics 0.68 (0.62 to 0.74). Conclusions: Performance of the GARFIELD-AF risk tool was superior to CHA2 DS2 -VASc in predicting stroke and mortality and superior to HAS-BLED for bleeding, overall and in lower risk patients. The GARFIELD-AF tool has the potential for incorporation in routine electronic systems, and for the first time, permits simultaneous evaluation of ischaemic stroke, mortality and bleeding risks. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier for GARFIELD-AF (NCT01090362 ) and for ORBIT-AF (NCT01165710 ).